Lightning; gods and sciences - Gomes, Chandima; Gomes, Ashen (2014)
This paper gives an account on the historical and regional social concepts on the natural atmospheric phenomenon of the lightning phenomenon. It explores the divine concepts induced on lightning by various communities. The investigation also looks into the mythical beliefs with the objective of analysing how such conceptual aspects affect the promotion of scientific rationales of lightning safety and protection in such societies. The facts presented explain the reasons that prevent some communities from developing logical thinking and analytical skills in the field of lightning science.